Hubungan Paparan Getaran Mekanis Dengan Kelelahan Kerja Dan Gangguan Kesehatan Pada Tenaga Kerja Bagian Produksi PT. Putri Indah Pertiwi Desa Pule, Gedong, Pracimantoro, Wonogiri - WIRA PURNAMA, ANGGA, Dr. Suwadji, M.Kes, Tarwaka, PGDip Sc, M.Erg (2015)
The process of industrialization and modernization of life with the increasingly widespread application of advanced technologies, among others, clearly visible from growing rapidly increasing use of diverse machinery and equipment mechanical work carried out by the motor. Machinery and equipment mechanical work raises the vibration is regular movement of objects or media with alternating direction from its equilibrium position. The purpose of this study was to determine the relationship of exposure to mechanical vibration at work fatigue and health problems in labor production PT. Putri Indah Pertiwi in the Pule village, Gedong, Pracimantoro, Wonogiri. This research method using observational design with cross-sectional approach. The study population was all male workers on the day shift production PT. Putri Indah Pertiwi numbered 17 people. The research sample is male-17 workers were taken by purposive sampling technique. Statistical test using Pearson Product Moment Correlation test with the results of the analysis obtained by value p = 0.00 <0.05 and a value of correlation r = 0.910 (significant, very strong) so that there is a connection with the mechanical vibration fatigue. Besides the values obtained p = 0.031 <0.05 and a value of correlation r = 0.522 (significant, moderate) so that no mechanical vibration relationship with health problems. Also obtained the value p = 0.008 <0.05 and a value of correlation r = 0.618 (significant, strong) so that no fatigue working relationship with health problems. With the results significant value and correlated, which means there is a correlation with exposure to mechanical vibration fatigue and health problems in labor production PT. Putri Indah Pertiwi in the Pule village, Gedong, Pracimantoro, Wonogiri.